Efektivitas Pemasaran Melalui Iklan Instagram terhadap Penjualan Booth dan Peningkatan Traffic: Studi Kualitatif pada Event Nite owl Market - Sindy Amelia; Arief Rachmansyah (Penerbit Jurnal Indonesia, 2026)
This study looks at how using Instagram ads for marketing can help boost sales at the booths and bring more people to the Nite Owl Market Event. The evolution of digital technology has fundamentally transformed the marketing landscape, establishing Instagram as an effective platform for reaching broad audiences and boosting sales. Employing a qualitative approach, this research explores the experiences, perceptions, and views of booth owners, event organizers, and visitors. The findings indicate that Instagram ads play a central role in Nite Owl Market's marketing strategy, successfully attracting both potential vendors and attendees. Event organizers actively leverage Instagram features to enhance reach and engagement, despite facing challenges like high competition and algorithm changes. The effectiveness of Instagram advertising is evidenced by increased visitor traffic and booth purchase decisions, driven by engaging visual content and clear information.